The abiotic factors effects on the development of primary roots, growth and survival of Rhizophora mangle L. propagules - Febles-Patrón, José Luis; Novelo López, Jorge; Batllori Sampedro, Eduardo (Instituto de Ecología, A.C., 2016)
An experiment was made to know the abiotic factors effect on the development of primary roots, growth and survival of red mangrove propagules (Rhizophora mangle L.). 180 propagules were collected at the Santa Clara swamp, in the North coast of Yucatan, Mexico, forming 6 groups of 30 individuals. Propagules were placed in orifices of a white exponded polyestirene sheet, maintaining them during 48 days in plastic containers, with a vertical position and with hipocotil immersed in water. There were considered three salinities: freshwater (5-7 ups), sea water (30-40 ups) and hypersaline water (70-75  ups), and two conditions of illumination (shade and direct solar radiation) with a maximum Albedo, representing a total of six treatments. Plants under shade conditions (SD, SM and SH) presented a survival of 100%, whereas the treatments exposed directly to solar radiation (LD, LM and LH) presented an inverse survival to the water salinity. Roots development was gradually less when increasing the salinity, intensifying when the propagules were exposed to direct radiation and a greater temperature of the water. The propagules at the shade-freshwater treatment (SD), presented a greater gain of weight due to the development of roots and leaves (only in this treatment leaves were developed). Salinity is the factor that controls the roots production in the R. mangle propagules at the establishment stage. Insolation and temperature cause an increase of physiological stress in the propagules, diminishing the production of roots and increasing mortality.